CORRELATION BETWEEN MELASMA AND QUALITY OF LIFE IN WOMEN IN SEBANI VILLAGE, TARIK DISTRICT, AND SIDOARJO DISTRICT - Utomo, Zelda Fidellia Natasha; Dian Putri, Maria Patricia; Suwandito, L (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Background: Melasma has another name chloasma, derived from the Greek word "melas" which means black. Melasma is usually found on the cheeks, forehead, nose, chin, and the area above the lip. The majority of melasma will appear in women who have dark skin with certain histories such as pregnancy, never using sunscreen resulting in exposure to ultraviolet (UV) rays, use of hormonal contraception.Purpose: Knowing the relationship between melasma and the quality of life of mothers in Sebani Village, Tarik District, Sidoarjo Regency.Methods: The design of this research is analytic observational using cross sectional method. The number of samples in the study were 67 people. Data analysis used the t-test and Spearman's correlation.Result: The results of the study found that most of the respondents aged 46-50 were 43 people (64.2%). The average MASI of people exposed to the sun >6 hours, namely 27.41, was higher than people exposed to the sun <6 hours, namely 18.09. The average MASI of people who do not use sunscreen, which is 27.41, is higher than those who do not use sunscreen, which is 18.09. The average MASI for people who use birth control pills is 28.47, higher than people who don't use birth control pills, which is 25.02.. The relationship between melasma and quality of life was analyzed using the Spearman correlation test and found r = 0.823 and p = 0.000.Conclusion: There is a very strong relationship between melasma and quality of life